(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article delves into the significance of syntactic analysis in instructing the grammatical structures of verbs, highlighting how grasping verb syntax improves language learners’ understanding and utilization of grammar principles. It examines different approaches to syntactic analysis and evaluates their efficacy within educational contexts.